Selected Decisions and Selected Documents of the International Monetary Fund, Fortieth Issue. (Selected Decisions; 40, 2019, 2019)
This volume is the Fortieth Issue of Selected Decisions and Selected Documents of the IMF. It includes decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF, as well as selected documents, to which frequent reference is made in the current activities of the IMF. In addition, it includes certain documents relating to the IMF, the United Nations, and other international organizations. As with other recent issues, the number of decisions in force continues to increase, with the decision format tending to be longer given the use of summings up in lieu of formal decisions. Accordingly, it has become necessary to delete certain decisions that were included in earlier issues, that is, those that only completed or called for reviews of decisions, those that lapsed, and those that were superseded by more recent decisions. Wherever reference is made in these decisions and documents to a provision of the IMF's Articles of Agreement or Rules and Regulations that has subsequently been renumbered by, or because of, the Second Amendment of the Fund's Articles of Agreement (effective April 1, 1978), the corresponding provision currently in effect is cited in a footnote.